Local and global factors in work stress—the Australian dairy farming examplar - Wallis, Alison; Dollard, Maureen F. (SJWEH Supplements, 2008)
' ' OBJECTIVES ': 'Whether the job demand–control model is necessary, but not sufficient, to explain farmers’ high levels of strain was studied. If the model were sufficient, then the impact of deregulation would mean that Australian dairy farmers would experience high-strain jobs rather than the active jobs reported for American and European farmers. ' ' METHODS ': 'Longitudinal survey data were used from 348 farmers in 2002 and 195 farmers matched in 2003. ' ' RESULTS ': 'The dairy farmers had extremely high distress levels, which increased significantly over 12 months (39% according to the General Health Questionnaire, binary scoring), exceeding those of several other Australian occupations. The dairy farmers had active jobs. This situation indicated that theoretically the job demand–control model was not sufficient to explain high levels of distress. Specific measures (globalization, finances, demands of work in sheds) explained the variance in psychological distress beyond the job demand–control theory cross-sectionally, whereas specific demands alone predicted distress over 12 months. In addition, specific demands increased significantly over 12 months. ' ' CONCLUSIONS ': 'The job demand–control model requires supplementation if the impact of important external or upstream factors such as globalization or free market forces, and environmental demands are to be fully assessed. Deregulation demands appear to be the most important and may have reached a ceiling of tolerance that cannot be moderated by control and that requires intervention upstream at the community, industry, and government level. The study builds knowledge, given that little previous research has used the job demand–control model to study self-employed or rural workers.
Keywords: Australia; dairy farmer; dairy farmer stress; dairy farming; demand–control model; farm stress; farmer; farming; global factor; job demand–control model; local factor; psychological distress; stress; work stress